Cognitive radio architecture : the engineering foundations of radio XML - Mitola, Joseph (Wiley-Interscience, 2006)
An exciting new technology, described by the one who invented it This is the first book dedicated to cognitive radio, a promising new technology that is poised to revolutionize the telecommunications industry with increased wireless flexibility.